Molecular Characterization of Rifampin- and Isoniazid-Resistant Mycobacterium tuberculosis Strains Isolated in Poland - Sajduda, Anna (J Clin Microbiol, 2004)
A total of 105 rifampin (RMP)- and/or isoniazid (INH)-resistant strains of Mycobacterium tuberculosis isolated from different parts of Poland in 2000 were screened for mutations associated with resistance to these drugs by two molecular methods, namely sequence analysis and real-time PCR technology. Three loci associated with drug resistance were selected for characterization: they were rpoB (RMP), katG, and the regulatory region of inhA (INH). Nineteen different mutations were identified in 64 RMP-resistant strains, and five new alleles were described. The most common point mutations were in codons 531 (41%), 516 (16%), and 526 (9%) of the rpoB gene. Mutations were not found in two (3%) of the isolates. In the case of resistance to INH, six different mutations in the katG gene of 83 resistant strains were detected. Fifty-seven (69%) isolates exhibited nucleotide substitutions at codon 315. One strain harbored a mutation affecting codon 279 (Gly279Thr). Twelve of 26 INH-resistant strains with the wild-type codon 315 (14.5% of all strains tested) had the mutation −15C→T in the regulatory region of inhA. A full correlation between the DNA sequence analysis and real-time PCR data was obtained. We conclude that the real-time PCR method is fast and reliable for the detection of RMP and INH resistance-associated mutations in M. tuberculosis clinical isolates.